1967
DOI: 10.2307/1933106
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and Fruiting in the White Oaks. Pistillate Flowering, Acorn Development, Weather, and Yields

Abstract: Female flowering and acorn development in three species of white oaks were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 8 publications
7
83
0
1
Order By: Relevance
“…The ontogenetic sequence from the apparition of flowers (in angiosperms) or strobili (in gymnosperms) to the time of fruit ripening or seed maturation involves a number of stages (i.e., pollination, fertilization, the growth and differentiation of the embryo; Pallardy 2008) that we group here under the term of fruit (or cone) maturation. The seasonality of fruit (cone) maturation (in terms of size and mass) is relatively well documented (see, e.g., Sharp andSpargue 1967, Fujii 1993 in temperate deciduous oaks; Troeng 1981, Koppel et al 1987 in boreal conifers), but there is scarce information regarding the environmental dependence of these processes. Temperature has been identified as a cue for both cone maturation (Mutke et al 2003) and seed maturation (Meunier et al 2007) in conifers.…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…The ontogenetic sequence from the apparition of flowers (in angiosperms) or strobili (in gymnosperms) to the time of fruit ripening or seed maturation involves a number of stages (i.e., pollination, fertilization, the growth and differentiation of the embryo; Pallardy 2008) that we group here under the term of fruit (or cone) maturation. The seasonality of fruit (cone) maturation (in terms of size and mass) is relatively well documented (see, e.g., Sharp andSpargue 1967, Fujii 1993 in temperate deciduous oaks; Troeng 1981, Koppel et al 1987 in boreal conifers), but there is scarce information regarding the environmental dependence of these processes. Temperature has been identified as a cue for both cone maturation (Mutke et al 2003) and seed maturation (Meunier et al 2007) in conifers.…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…During hyperphagia, masting plant species that produce acorns, nuts, and berries provide bears with high caloric energy that is critical for survival and reproduction (Rogers et al 1976, Inman and Pelton 2002, McDonald and Fuller 2005, Mosnier et al 2008. But mast crops can fail due to unfavorable weather conditions, e.g., late-spring freezes and droughts (Sharp andSprague 1967, Neilson andWullstein 1980), or disease outbreaks (Liebhold et al 2000), resulting in bears seeking alternative food sources (Baruch-Mordo et al 2014). Use of anthropogenic food resources can lead to behavioral adaptations and changes to bear ecology Berger 2003a, Baruch-Mordo et al 2014) and result in increased human-bear conflict (Oka et al 2004, Baruch-Mordo et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Ecologists often call the phenomenon of producing good crops some years and poor crops in other years, mast-seeding or mast-fruiting (Janzen, 1971;Silvertown, 1980 demonstrated that weather has strong impact (Goodrum et al, 1971;Minima, 1954;Romashov, 1957;Sharp and Chisman, 1961;Sharp and Sprague, 1967 Christisen and Kearby,1984) beneath the canopy of each tree so that they were scattered throughout the canopy but not beneath the canopy of neighboring conspecifics. The total trap area sampled was on average ca 7.5% of the canopy (range: 4-19% Romashov, 1957).…”
Section: Introductionmentioning
confidence: 99%